(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: Internet has revolutionized the way the world accesses information and it is common for parents of young children to use the Internet to seek medical advice when their child is ill. There is very little data on how this influences the subsequent management of the illness. The aim of this study was to study the role of the Internet in the health-seeking behaviour of parents of under-five children during fever. Methodology: 250 parents of children under five, with fever who presented to the Paediatric OPD were interviewed with a semi-structured questionnaire on their health-seeking behaviour and internet utilisation for health information. A semistructured questionnaire was used to interview the parents. Statistical analysis was done using SPSS version 16.0. Results: 54.4% parents used the Internet for health information.78.68% go through the first few sites shown by the search engine without knowing the name of the site or the credibility of the source. Internet-users were more likely to use a thermometer to record body temperature and know the temperature that denoted fever. There was no difference in the health seeking behaviour or initial action taken at home in the two groups. The positive health-care seeking behaviour of the mother was found to be related only to her education. Conclusion: A large group of parents use the Internet for health information but do not know how to assess the credibility of the sources. Most parents used the information only to supplement the doctors’ advice and not as a replacement.